Effect of Modifying Prosthetic Socket Base Materials by Adding Nanodiamonds - Lifang Ma; Xiaogang Hu; Shizhong Zhang; Yu Chen (Journal of Chemistry)
The curing process of prosthetic socket base materials requires attention owing to a series of associated problems that are yet to be addressed and solved. However, to date, few relevant studies have been reported. In this paper, nanodiamonds modified with a silane coupling agent were dispersed into a prosthetic socket base material, and the performance of the modified base materials was investigated. Adding a predetermined amount of nanodiamonds to the prosthetic socket base material increased the glass transition temperature, improved the mechanical properties of the cured base material, and reduced the influence of the volatile gas formed during the curing process on the environment. With increasing nanodiamond contents, the glass transition temperature increased and the mechanical properties improved slightly. Owing to the high thermal conductivity of the nanodiamonds, the localized heat, as a result of the curing process, could be dissipated and released. Thus, adding nanodiamonds led to a more uniform temperature field forming in the curing system. This improved the curing process and reduced the formation of volatile monomers, thereby decreasing the adverse impact of the generated volatile gases on the environment. All of these provide a potential strategy for modifying prosthetic socket base materials.